Nitrogen Fixation Methods and Protocols - Ribbe, Markus W.; Ribbe, Markus W. (Methods in Molecular Biology,, 2011)
Few problems in protein biochemistry have proven to be as challenging and recalcitrant as the molecular description of nitrogenase, the catalyst of one of the most remarkable chemical transformations in biological systems: the nucleotide-dependent reduction of atmospheric dinitrogen to bioavailable ammonia.  In Nitrogen Fixation: Methods and Protocols, recognized experts in the field provide an up-to-date, in-depth overview of the methods that have been applied to studying the nitrogenase at a molecular level, ranging from genetic, biochemical, spectroscopic, and chemical methods to theoretical calculations. In addition, techniques used to study an enzyme system that is homologous to nitrogenase are described in this book.  Written in the highly successful Methods in Molecular Biology™ series format, methods chapters include introductions to their respective chapters, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and cutting-edge, Nitrogen Fixation: Methods and Protocols will be useful for anyone interested in nitrogenase research and willing to venture further toward addressing the remaining mechanistic and biosynthetic questions of this fascinating enzyme system.